Genetic Polymorphisms in Autophagy-Associated Genes in Korean Children With Early-Onset Crohn Disease. Issue 3 (September 2015) - Na, So Young; Park, Sung Sup; Seo, Jeong Kee
ABSTRACT Objective: The aim of the present study was to investigate the genetic polymorphisms of the autophagy-associated genes autophagy-related 16-like 1 (ATG16L1), immunity-related GTPase M (IRGM), Unc-51-like kinase 1 (ULK1), and NOD2 with respect to early-onset Crohn disease (CD) among Korean children. Methods: A total of 65 patients with CD from the Seoul National University Children's Hospital, from January 2000 to May 2012, and 72 unaffected controls were selected. Twelve different single nucleotide polymorphisms (SNPs) were analyzed (TaqMan assay: ATG16L1 rs2241880, IRGM SNPs [rs13361189, rs4958847, rs1000113, rs10065172, and rs72553867], ULK1 SNPs [rs12303764, rs10902469, and rs7488085], NOD2 SNPs [Arg702Trp and Gly908Arg]; direct sequencing: NOD2 leu1007fsinsC). The onset age of patients was 8.6 ± 4.7 years. Twelve patients (18.5%) had an onset age of <1 year. Results: Two of the 12 SNPs showed significant results. IRGM rs1000113 exhibited an association with CD with respect to its minor allele frequency (odds ratio [OR] 1.71, 95% confidence interval [CI] 1.05–2.79, P = 0.03) and genotype distribution (dominant model: OR 2.17, 95% CI 1.07–4.39, P = 0.03). IRGM rs72553867 exhibited association with CD with respect to its minor allele frequency (OR 0.50, 95% CI 0.27–0.91, P = 0.02) and genotype distribution (dominant model: OR 0.50, 95% CI 0.23–0.94, P = 0.03). The 3 SNPs of NOD2 existed only as wild types for both groups. In the genotype-phenotype analysis, the onset age, disease location, and disease behavior exhibited no association. Conclusions: IRGM rs1000113 and IRGM rs72553867 exhibited associations with early-onset CD as risk loci and defense loci, respectively. This suggests that the autophagy pathway plays an important role in early-onset CD.